Microatlas - Mustafa Kamil, Afiqah; Ahmad Shukri, Nur Shahirah; Isfak Ahmad, Ayu Nursuria; Ismail, Athifah; Khair Yusof, Nur Farrah Nabilah; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Microatlas is an educational tool that able to enhance learning. The target users are the school students, age 11 to 15 years old as this tool combines the knowledge of geography and introduces microbes to the users. Microatlas mobile app can be downloaded to scan the puzzle that forms the globe of the world and animation on the microbial ecology will then appear via augmented reality. Microatlas is an interactive and fun way of learning.